Comparative analysis of prominent English listening websites used by Indonesian EFL higher education students - Rizaldy Hanifa; Siti Rahimah Yusra (Studies in English Language and Education, 2026)
In English as a foreign language (EFL) education, the limited classroom time allocated for listening practices restricts students’ exposure to essential auditory input, potentially impeding their language acquisition. Autonomous listening practices utilizing digital resources are essential for addressing this issue. The extensive range of available websites presents difficulties in identifying pedagogically valuable options. This research sought to evaluate four frequently utilized websites by Indonesian higher education students, British Council, TED Talks, BBC Learning English, and English with Lucy, for the purpose of independent listening practice. The study employed a document analysis approach within a qualitative research framework, utilizing an evaluation checklist. The data were analysed using qualitative content analysis to assess each website’s pedagogical effectiveness, usability, and alignment with listening skill development, providing a comparative evaluation to inform best practices in EFL listening resource selection. The findings indicate distinctive strengths from each platform including proficiency-specific resources, authentic materials, multilingual subtitles, offline accessibility, multimedia engagement, operational efficiency, and user-friendly interfaces. Limitations noted include the absence of collaborative features, insufficient scaffolding for novices, limited feedback mechanisms, restricted linguistic diversity, and inconsistent navigation. These results underscore the platforms’ potential to enhance EFL listening skills while highlighting areas for development. It is essential for educators and learners to critically evaluate EFL websites to optimize their advantages in their teaching and learning context. The research supports the incorporation of interactive elements, adaptive pathways, and culturally inclusive content to meet the varied needs of learners and ensure alignment of digital resources with global pedagogical standards.